Seasonal Fluctuations as a Result of Changes in the Investor Structure – A Case Study for the Warsaw Stock Exchange S.A. - Szczepańska-Przekota, Anna (Journal of Finance and Financial Law, 2023)
The purpose of the article. Seasonality in capital markets is described in the financial literature as a type of calendar anomaly that indicates irrational investor behaviour. One might ask whether there are reasons other than irrational investor behaviour for changes in the occurrence and magnitude of calendar anomalies. The paper hypothesises that changes in the structure of investors are responsible for the occurrence of seasonal anomalies. Methodology. The analysis of seasonal fluctuations in the WIG index quotations for the years 1997–2022 was carried out using the CENSUS X12 procedure, with tests for the stability of seasonal fluctuations and the presence of moving seasonality. The assessment of the relationship between the strength of seasonal fluctuations, measured by the difference between the monthly extreme seasonal deviations in a given year, and the share of individual investors in the total number of stock market transactions on the Warsaw Stock Exchange was carried out using the Pearson linear correlation coefficient and the Granger causality test. Results of the research. Periods of appearance and disappearance of seasonal fluctuations on the Polish stock market have been observed. Changes in the structure of investors were proposed as an explanation for this phenomenon. The periods in which the seasonality phenomenon was more intense coincided with the increased activity of individual investors. Therefore, it was not the description of the anomaly that was the reason for its disappearance, but its appearance and disappearance was linked to the structure of investors who showed certain constant behaviours.